Reviewing South Africa’s Non-Proliferation Policy and Strategic Trade Controls - Melanie Reddiar (The Thinker)
The prohibition of Weapons of Mass Destruction (WMDs) in South Africa is governed through the implementation of an integrated and robust non-proliferation and arms control policy, legislative and regulatory framework, which has been revised and improved over time to address global developments; scientific and technological developments; and advancement of the threat landscape in terms of illicit trafficking of restricted goods and technologies as well as terrorism. Nonetheless, deficiencies in the regulatory framework and legislation became apparent over the years, especially after the infiltration of the South African industry by the A.Q. Khan nuclear smuggling network. Although some of these deficiencies have been addressed, others are more challenging and require further work to be concluded in order to improve regulatory processes and strengthen the non-proliferation system, and to ensure that the proliferation strategies of non-state actors can be combatted. It is also aimed at South Africa maintaining its image as a reliable and responsible supplier, recipient and end user of strategic goods and technologies, while contributing meaningfully to global efforts of disarmament and non-proliferation of WMDs as a responsible member of the international community, as an advocate for global disarmament, and as a leader in efforts to prevent the proliferation of WMDs, in general.